111k views
3 votes
1. Solve 6(x - 2) = 2(x + 12).

2 Answers

5 votes

Answer:ok so. X= 9.

Step-by-step explanation: Step by Step Solution

More Icon

Reformatting the input :

Changes made to your input should not affect the solution:

(1): Dot was discarded near ").".

Rearrange:

Rearrange the equation by subtracting what is to the right of the equal sign from both sides of the equation :

6*(x-2)-(2*(x+12))=0

Step by step solution :

STEP

1

:

Equation at the end of step 1

(6 • (x - 2)) - 2 • (x + 12) = 0

STEP

2

:

Equation at the end of step 2

6 • (x - 2) - 2 • (x + 12) = 0

STEP

3

:

STEP

4

:

Pulling out like terms

4.1 Pull out like factors :

4x - 36 = 4 • (x - 9)

Equation at the end of step

4

:

4 • (x - 9) = 0

STEP

5

:

Equations which are never true:

5.1 Solve : 4 = 0

This equation has no solution.

A a non-zero constant never equals zero.

Solving a Single Variable Equation:

5.2 Solve : x-9 = 0

Add 9 to both sides of the equation :

x = 9

One solution was found :

x = 9

here you go

User Pratheesh
by
6.3k points
4 votes

Answer:

6x-12=2x+24

combine like terms

4x-12=24

add 12 on both sides

4x=36

divide by 4

answer is:x=9

Explanation:

User Malfist
by
5.3k points